Effect of Processing Parameters on Performance of Spray-Deposited Organic Thin-Film Transistors - Jack W. Owen; Natalia A. Azarova; Marsha A. Loth; Markos Paradinas; Mariona Coll; Carmen Ocal; John E. Anthony; Oana D. Jurchescu (Journal of Nanotechnology)
The performance of organic thin-film transistors (OTFTs) is often strongly dependent on the fabrication procedure. In this study, we fabricate OTFTs of soluble small-molecule organic semiconductors by spray-deposition and explore the effect of processing parameters on film morphology and device mobility. In particular, we report on the effect of the nature of solvent, the pressure of the carrier gas used in deposition, and the spraying distance. We investigate the surface morphology using scanning force microscopy and show that the molecules pack along the π-stacking direction, which is the preferred charge transport direction. Our results demonstrate that we can tune the field-effect mobility of spray-deposited devices two orders of magnitude, from 10−3 cm2/Vs to 10−1 cm2/Vs, by controlling fabrication parameters.